Hubungan Mmasa Kerja dan Tingkat Kebisingan dengan Nilai Ambang Pendengaran dan Gangguan Pendengaran Tenaga Kerja Wanita pada Unit Tenun - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
PT. Samitex Yogyakarta is a company, who produces unbleached plain textile. In the production process, mainly in the weaving department, there is noise, which is more than the limit that is 85 dBA. If this goes continuously for long time, it may excess of the worker's hearing limitation, causes a hearing disturbance. This research purposed to know: (1) the relationship of the noisy level with the value of hearing limitation